The Routledge Handbook of the Economics of Ageing (Taylor & Francis, 2024)
Ageing populations pose some of the foremost global challenges of this century. Drawing on an international pool of scholars, this cutting-edge Handbook surveys the micro, macro and institutional aspects of the economics of ageing. Structured in seven parts, the volume addresses a broad range of themes, including health economics, labour economics, pensions and social security, generational accounting, wealth inequality and regional perspectives. Each chapter combines a succinct overview of the state of current research with a sketch of a promising future research agenda. This Handbook will be an essential resource for advanced students, researchers and policymakers looking at the economics of ageing across the disciplines of economics, demography, public policy, public health and beyond.
English
Keywords: Age groups: the elderly; Economics; Labour / income economics; Medicolegal issues; Population and demography; economics of ageing,labour economics,generational accounting,health economics,Population Ageing,NTA,Pension Systems,Health Deficits,Pension Reforms,Assortative Matching,Younger Men,Labor Income,Normal Retirement Age,Public Transfers,Income Replacement Rate,OLG Model,Life Cycle Model,Age Profiles,Human Development Index,Retirement Age,Frailty Index,Dependency Ratio,Spousal Health,Differential Mortality,Vice Versa,Public Pension,Effective Retirement Ages,Healthcare Spending,Demographic Transition